Creepy creatures & bizarre beasts from the Bible - Osborne, Rick.; Strauss, Ed, 1953-; Carpenter, Anthony (Grand Rapids, Mich. : Zonderkidz, 2004)
A light-hearted look at the animals of the Bible, from those of Noah's ark to sacrificial bulls, and what their stories reveal about God and our relationship with Him.
Bible animals -- Amazing unreal creatures -- Sacrificial animals.
Keywords: Animals in the Bible -- Juvenile literature; Children -- Conduct of life; Animals in the Bible; Conduct of life